Role of nitric oxide in interleukin 2-induced corticotropin-releasing factor release from incubated hypothalami. - Karanth, S (1993)
Stimulation of corticotropin-releasing factor (CRF) release from the hypothalamus by interleukin 2 (IL-2) was recently demonstrated. Cytokines induce nitric oxide synthase (NOS), an enzyme that converts L-arginine into L-citrulline and nitric oxide (NO). NO is believed to be responsible for the cytotoxic action of these agents. The constitutive form of NOS occurs in neurons in the central nervous system and NO appears to play a neurotransmitter role in cerebellar and hippocampal function. We explored the probability that IL-2 and synaptic transmitters might release CRF via NO. The effects of L-arginine, the substrate for NOS, and NG-monomethyl-L-arginine (NMMA), a competitive inhibitor of NOS, on IL-2-induced CRF release were studied using mediobasal hypothalami (MBHs) incubated in vitro in Krebs-Ringer bicarbonate buffer. L-Arginine did not alter basal and IL-2-induced CRF release after 30 min of incubation but significantly elevated both basal and IL-2-induced CRF release when MBHs were incubated 30 min longer, presumably because the endogenous substrate had been depleted after the initial 30-min incubation period. In 30-min incubations, both carbachol, an acetylcholineomimetic drug, and norepinephrine stimulated CRF release. There was an additive effect of incubation of the MBHs in the presence of carbachol (10(-7) M) and IL-2 (10(-13) M). On the other hand, coincubation of MBHs with norepinephrine (10(-6) M) and IL-2 (10(-13) M) did not produce any additive effect. Addition of NMMA, an inhibitor of NOS, at 1 or 3 x 10(-4) M completely suppressed IL-2-induced release of CRF as well as that caused by IL-2 plus carbachol. In contrast, the release of CRF induced by norepinephrine was not blocked by 3 x 10(-4) M NMMA. The data indicate that IL-2 can activate constitutive NOS leading to increased NO release, which activates CRF release. It appears that NO is also involved in the release of CRF induced by carbachol but not by norepinephrine.